Union of the Comoros : Enhanced Initiative for Heavily Indebted Poor Countries: Completion Point Document and Multilateral Debt Relief Initiative. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2013)
In June 2010, the International Development Association (IDA) and the IMF agreed that Comoros had met the requirements for reaching the decision point under the Enhanced Heavily Indebted Poor Countries (HIPC) Initiative. As a result of the debt reconciliation exercise for the completion point, the present value of eligible external debt at end-2009 has been revised upward. Full delivery of HIPC assistance together with additional bilateral assistance beyond HIPC and Multilateral Debt Relief Initiative (MDRI) debt relief at the completion point would reduce Comoros' external debt burden significantly.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet